2016
DOI: 10.1002/eat.22634
|View full text |Cite
|
Sign up to set email alerts
|

Application of structural equation mixture modeling to characterize the latent structure of eating pathology

Abstract: These findings indicate that there is substantial variability in the phenomenology of traditional DSM-based ED categories across latent profiles, and highlight the salience of certain ED phenotypes that have been debated in the literature. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:542-550).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…First, a comprehensive review of taxometric research concluded that there is little support for discrete groups within the continuously distributed internalizing and externalizing spectra, as well as normal and maladaptive personality, although the evidence was less conclusive for schizotypy and substance use (Haslam, Holland, & Kuppens, 2012). Second, studies using latent variable modelling approaches also generally find that dimensional models fit data better than categorical models, in particular for disorders from the internalizing and externalizing spectra (Aslinger, Manuck, Pilkonis, Simms, & Wright, 2018;Conway, Hammen, & Brennan, 2012;Eaton et al, 2013;Krueger, Markon, Patrick, & Iacono, 2005;Luo, Donnellan, Burt, & Klump, 2016;Wright et al, 2013), although there is also some evidence of discontinuity (Forbes, Baillie, & Schniering, 2016;Forbush & Wildes, 2017;Klein & Kotov, 2016). Individual symptoms have typically also been found to be continuous rather than binary (Flett, Vredenburg, & Krames, 1997;Van Os, Linscott, Myin-Germeys, Delespaul, & Krabbendam, 2009).…”
Section: Hierarchical and Quantitative Genetic Architecture -Evidencementioning
confidence: 99%
“…First, a comprehensive review of taxometric research concluded that there is little support for discrete groups within the continuously distributed internalizing and externalizing spectra, as well as normal and maladaptive personality, although the evidence was less conclusive for schizotypy and substance use (Haslam, Holland, & Kuppens, 2012). Second, studies using latent variable modelling approaches also generally find that dimensional models fit data better than categorical models, in particular for disorders from the internalizing and externalizing spectra (Aslinger, Manuck, Pilkonis, Simms, & Wright, 2018;Conway, Hammen, & Brennan, 2012;Eaton et al, 2013;Krueger, Markon, Patrick, & Iacono, 2005;Luo, Donnellan, Burt, & Klump, 2016;Wright et al, 2013), although there is also some evidence of discontinuity (Forbes, Baillie, & Schniering, 2016;Forbush & Wildes, 2017;Klein & Kotov, 2016). Individual symptoms have typically also been found to be continuous rather than binary (Flett, Vredenburg, & Krames, 1997;Van Os, Linscott, Myin-Germeys, Delespaul, & Krabbendam, 2009).…”
Section: Hierarchical and Quantitative Genetic Architecture -Evidencementioning
confidence: 99%
“…We defined “at-risk binge eating” as averaging one or more objective binge eating episodes per month over the previous 3 months. We chose this definition because it is less than the frequency required for a DSM–5 diagnosis of binge eating disorder or bulimia nervosa (American Psychiatric Association, 2013), and research suggests that those who binge eat tend to be qualitatively different from those with other forms of eating pathology (Forbush & Wildes, 2016; Gleaves, Brown, & Warren, 2004), which suggests that any frequency of binge eating may be clinically significant. We defined “at-risk gambling” as meeting at least one of the following criteria over the past year: engaging in at least four gambling activities, gambling in a casino or using slot machines, spending > $153.50 on gambling, or gambling at least four times per month.…”
Section: Methodsmentioning
confidence: 99%
“…Eating disorders (EDs) are among the most medically compromising psychiatric illnesses (Harris & Barraclough, 1998; Smink, van Hoeken, & Hoek, 2013) and are characterized by substantial heterogeneity in symptoms (Dechartres et al, 2011; Forbush & Wildes, 2016). When patients are grouped into empirically derived latent groups according to their symptom profiles, group membership is predictive of symptom remission, readmission, and mortality (Escobar‐Koch et al, 2010; Peterson et al, 2013; Sysko, Hildebrandt, Wilson, Wilfley, & Agras, 2010).…”
Section: Introductionmentioning
confidence: 99%